2015
DOI: 10.3109/00016489.2014.993090
|View full text |Cite
|
Sign up to set email alerts
|

Imaging cochlear implantation with round window insertion in human temporal bones and cochlear morphological variation using high-resolution cone beam CT

Abstract: Conclusions: The present experimental set-up of high spatial resolution cone-beam computed tomography (CBCT) showed advantages of demonstrating the critical landmarks of the cochlea in identifying the position of intracochlear electrode contacts and has the potential for clinical application in cochlear implant (CI) surgery. Objective: To evaluate a newly developed CBCT system in defining CI electrode array in human temporal bone and cochlear morphological variation. Methods: Standard electrode, flexible tip e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 12 publications
3
29
0
6
Order By: Relevance
“…An exact understanding of the labyrinth's inner structure is difficult to ascertain due to its complexity and the investing hard surrounding temporal bone. To understand its structural framework, researchers and surgeons have had to rely on illustrations derived from 2 dimensional histological images, 3‐dimensional reconstruction of labyrinthine bone and surgical dissection images (Buytaert et al, ; Lee et al, ; Zou et al, ). However, histopathologic studies of the membranous labyrinth have been limited to 2‐dimensional staining methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An exact understanding of the labyrinth's inner structure is difficult to ascertain due to its complexity and the investing hard surrounding temporal bone. To understand its structural framework, researchers and surgeons have had to rely on illustrations derived from 2 dimensional histological images, 3‐dimensional reconstruction of labyrinthine bone and surgical dissection images (Buytaert et al, ; Lee et al, ; Zou et al, ). However, histopathologic studies of the membranous labyrinth have been limited to 2‐dimensional staining methods.…”
Section: Discussionmentioning
confidence: 99%
“…Most morphological analyses use 2‐dimensional images created through histological methods, even though 3‐dimensional techniques exist. For examples, micro CT, scanning Thin‐Sheet Laser Imaging Microscopy, optical micro‐angiography, optical coherence tomography and scanning laser optical tomography have all been tried as 3‐dimensional tools to understand the anatomy and demonstrate the relationship among the various structures (Buytaert, Johnson, Dierick, Salih, & Santi, ; Choudhury, Chen, Shi, Nuttall, & Wang, ; Lee et al, ; Lee, Park, Kang, & Choung, ; Tinne et al, ; Zou et al, ). Unfortunately, these, computer‐assisted reconstructed images have provided limited information when trying to study the in vivo anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…Rated as: -= not visible, += poorly, ++= moderately and +++= good visible. (6) (54) visualization of the cochlear partitioning (9). A recent paper by Maillot et al (12) indicated that MDCT allows radiologists to examine the complex anatomy of the temporal bone with sub-millimeter resolution and is the first modality of choice.…”
Section: Ctmentioning
confidence: 99%
“…CBCT appears to provide sufficient spatial accuracy for intraoperative usage during temporal bone surgery (32) (27). Identifying the location of implants is becoming increasingly important in modern otology, which involves applications such as the Vibrant Soundbridge implant and CI (6,33) They showed that insufficient image-quality scores were more frequent in low-dose scans versus high-dose scans, however, the difference was only statistically significant for otologists but not for neuroradiologists. Image quality was critical for small structures (such as the stapes or lamella at the internal auditory canal fundus).…”
Section: Cbctmentioning
confidence: 99%
See 1 more Smart Citation